2012
DOI: 10.1029/2012wr012431
|View full text |Cite
|
Sign up to set email alerts
|

Direct geoelectrical evidence of mass transfer at the laboratory scale

Abstract: [1] Previous field-scale experimental data and numerical modeling suggest that the dual-domain mass transfer (DDMT) of electrolytic tracers has an observable geoelectrical signature. Here we present controlled laboratory experiments confirming the electrical signature of DDMT and demonstrate the use of time-lapse electrical measurements in conjunction with concentration measurements to estimate the parameters controlling DDMT, i.e., the mobile and immobile porosity and rate at which solute exchanges between mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 54 publications
(71 reference statements)
0
42
0
Order By: Relevance
“…In the PNM, we represent intergranular and intragranular porosity as different classes of pores, class 1 and 2, respectively. Whereas each intergranular connection occurs through a single bond between adjacent pores, intragranular connections are divided between a number ( N B ) of small bonds, consistent with CT scan visualizations of zeolite grains [ Swanson et al ., , ]. Grains are represented as regions of class 2 pores with diameters based on the α SRMT from Briggs et al [] and the formula for the diffusive length scale of a spherical grain, lD=15Dtrue/α 0.5 cm [ Haggerty et al ., ].…”
Section: Pore Network Modelingmentioning
confidence: 99%
“…In the PNM, we represent intergranular and intragranular porosity as different classes of pores, class 1 and 2, respectively. Whereas each intergranular connection occurs through a single bond between adjacent pores, intragranular connections are divided between a number ( N B ) of small bonds, consistent with CT scan visualizations of zeolite grains [ Swanson et al ., , ]. Grains are represented as regions of class 2 pores with diameters based on the α SRMT from Briggs et al [] and the formula for the diffusive length scale of a spherical grain, lD=15Dtrue/α 0.5 cm [ Haggerty et al ., ].…”
Section: Pore Network Modelingmentioning
confidence: 99%
“…These experiments are only indirectly sensitive to less-mobile porosity dynamics as fluid sampling preferentially pulls from the mobile-porosity domain. Geoelectrical measurements that are directly sensitive to conductive tracer exchange with less-mobile porosity have been demonstrated in laboratory (Swanson et al 2012) and field (Briggs et al 2013b) experiments. Geoelectrical measurements that are directly sensitive to conductive tracer exchange with less-mobile porosity have been demonstrated in laboratory (Swanson et al 2012) and field (Briggs et al 2013b) experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work at pilot field [ Singha et al ., ] and laboratory scales [ Swanson et al ., ] has demonstrated that anomalous solute transport has an observable geoelectrical signature that, in principle, can be exploited to directly determine mass transfer parameters (i.e., rate coefficient, mobile porosity, and immobile porosity) [ Day‐Lewis and Singha , ]. Whereas, fluid sampling preferentially draws from the mobile domain, electrical measurements are sensitive to solute tracer in both mobile and immobile domains.…”
Section: Introductionmentioning
confidence: 99%
“…Swanson et al . [] recently inferred mass transfer parameters using parametric sweeps for controlled homogeneous column experiments with independently evaluated immobile porosity. Forward simulations of transport were run for several thousand combinations of mass transfer parameters, and the fit to experimental data was evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation